Data Logic Structure and Key Technologies on Intelligent High-precision Map - LIU Jingnan,ZHAN Jiao,GUO Chi,LEI Tingting,LI Ying (Journal of Geodesy and Geoinformation Science, 2020)
Taking autonomous driving and driverless as the research object, we discuss and define intelligent high-precision map. Intelligent high-precision map is considered as a key link of future travel, a carrier of real-time perception of traffic resources in the entire space-time range, and the criterion for the operation and control of the whole process of the vehicle. As a new form of map, it has distinctive features in terms of cartography theory and application requirements compared with traditional navigation electronic maps. Thus, it is necessary to analyze and discuss its key features and problems to promote the development of research and application of intelligent high-precision map. Accordingly, we propose an information transmission model based on the cartography theory and combine the wheeled robot’s control flow in practical application. Next, we put forward the data logic structure of intelligent high-precision map, and analyze its application in autonomous driving. Then, we summarize the computing mode of “Crowdsourcing+Edge-Cloud Collaborative Computing”, and carry out key technical analysis on how to improve the quality of crowdsourced data. We also analyze the effective application scenarios of intelligent high-precision map in the future. Finally, we present some thoughts and suggestions for the future development of this field.